Development of a polystyrene phantom for quality assurance of a Gamma Knife® - Yona Choi; Kook Jin Chun; Jungbae Bahng; Sang Hyoun Choi; Gyu Seok Cho; Tae Hoon Kim; Hye Jeong Yang; Yeong Chan Seo; Hyun-Tai Chung (Nuclear Engineering and Technology, 2023)
A polystyrene phantom was developed following the guidance of the International Atomic Energy Association (IAEA) for gamma knife (GK) quality assurance. Its performance was assessed by measuring the absorbed dose rate to water and dose distributions. The phantom was made of polystyrene, which has an electron density (1.0156) similar to that of water. The phantom included one outer phantom and four inner phantoms. Two inner phantoms held PTW T31010 and Exradin A16 ion chambers. One inner phantom held a film in the XY plane of the Leksell coordinate system, and another inner phantom held a film in the YZ or ZX planes. The absorbed dose rate to water and beam profiles of the machine-specific reference (msr) field, namely, the 16 mm collimator field of a GK Perfexion™ or Icon™, were measured at seven GK sites. The measured results were compared to those of an IAEA-recommended solid water (SW) phantom. The radius of the polystyrene phantom was determined to be 7.88 cm by converting the electron density of the plastic, considering a water depth of 8 g/cm2. The absorbed dose rates to water measured in both phantoms differed from the treatment planning program by less than 1.1%. Before msr correction, the PTW T31010 dose rates (PTW Freiberg GmbH, New York, NY, USA) in the polystyrene phantom were 0.70 (0.29)% higher on average than those in the SW phantom. The Exradin A16 (Standard Imaging, Middleton, WI, USA) dose rates were 0.76 (0.32)% higher in the polystyrene phantom. After msr correction factors were applied, there were no statistically significant differences in the A16 dose rates measured in the two phantoms; however, the T31010 dose rates were 0.72 (0.29)% higher in the polystyrene phantom. When the full widths at half maximum and penumbras of the msr field were compared, no significant differences between the two phantoms were observed, except for the penumbra in the Y-axis. However, the difference in the penumbra was smaller than variations among different sites. A polystyrene phantom developed for gamma knife dosimetry showed dosimetric performance comparable to that of a commercial SW phantom. In addition to its cost effectiveness, the polystyrene phantom removes air space around the detector. Additional simulations of the msr correction factors of the polystyrene phantom should be performed.